A study of morphometric evaluation of the Son basin, India using geospatial approach - Kumar Rai P.; Narayan Mishra V.; Mohan K. (My University, 2025)
This study deals that morphometric evaluation is feasible method of characterization of hydrological response behavior of the any river basin. In this study, Son basin a tributary of the Ganga river has been selected for the detailed morphometric evaluation. The Son basin is approximate 68,863 km2 and shows sub-dendritic to dendritic drainage pattern. The measurement and analysis for Son basin and its five major sub-watershed are carried on GIS platform to describe the topography and drainage characteristics. The input parameters required to run this model are: a pour point, a minimum upstream area in sq km and a digital elevation model. Streams were automatically extracted from ASTER DEM data. The stream order of the basin is predominantly controlled by physiographic and structural conditions. The study area is designated as sixth-order basin and lower order streams mostly dominate the basin with the drainage density value of 0.26 km/km2. The slope of basin varied from 0° to 70.4° and the slope variation is mainly controlled by the local geology and erosion cycles. The bifurcation ratio (Rb) for the Son basin varies from 2.41 to 7. The higher values of Rb in basin indicate a strong structural and geological control on the drainage pattern. The elongation ratio of the basin is 0.553 indicating that the study area is extended with moderate to steep slopes. The increase in stream length ratio from lower to higher order shows that the basin is part of a mature geomorphic stage. © 2017 Elsevier B.V.